Oh, it sounds like you're working on your Spanish studies! Remember, it's important to try your best and learn at your own pace. If you're having trouble with specific questions, I encourage you to ask your teacher or classmates for help. Keep practicing and soon you'll see improvement!
-2b + 7 -3b = 2 -2b +7 -3b +2b = 2 + 2b 7 -3b + 3b = 2 + 2b +3b 7-2 = 2-2 + 2b + 3b 5 = 5b 1 = b
a = 3b - c a + c = 3b - c + c a + c = 3b (a + c)/3 = 3b/3 ( a + c ) / 3 = b Do your homework.
To simplify the expression 3b^2 - 3b, we first factor out the common factor of 3b. This gives us 3b(b - 1), where b - 1 is the simplified form of the expression. This expression represents the difference between 3 times the square of a variable b and 3 times the variable b.
3a + (3b - 2a) + 5b =3a + 3b - 2a + 5b =(3a - 2a) + (3b + 5b) =a + 8b
I need to study for this capítulo
Oh, it sounds like you're working on your Spanish studies! Remember, it's important to try your best and learn at your own pace. If you're having trouble with specific questions, I encourage you to ask your teacher or classmates for help. Keep practicing and soon you'll see improvement!
Oh, it sounds like you're working on some Spanish activities! Remember, the joy is in the journey of learning and exploring new things. Take your time, enjoy the process, and trust in your ability to find the answers within yourself. Happy painting!
Just put the name of the food... usually your teacher will introduce the names of the foods used in these pictures. Example : Problem number 1 says: Te Gustan ( guisantes ) No, ( no me gusta guisantes ) You just have to fill in the lines will the "Best answer", its not a thing that has the same answer. just fill it in with what you know.
6b^2 - 3b / 3b 6b^2 - 1 or ( 6b^2 - 3b) / 3b = 2b - 1 Or (6b^2 - 3b ) / 3b = 3b(2b - ) / 3b = 2b - 1
Since 3b is a factor of 9b, it is automatically the GCF.
-2b + 7 -3b = 2 -2b +7 -3b +2b = 2 + 2b 7 -3b + 3b = 2 + 2b +3b 7-2 = 2-2 + 2b + 3b 5 = 5b 1 = b
a = 3b - c a + c = 3b - c + c a + c = 3b (a + c)/3 = 3b/3 ( a + c ) / 3 = b Do your homework.
If 3b = 39 thenb = 39/3b = 13.
3b
3b-8b = -5
10ax-3b = 7